2020
DOI: 10.15283/ijsc19139
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Promotes cAMP Production in Mesenchymal Stem Cells by Regulating ADCY2

Abstract: Background and Objectives: The maternal-fetal interface is an important source of mesenchymal stem cells (MSCs), and it is influenced by high levels of estradiol (E2) during pregnancy. It is highly important to study the role of E2 in MSCs for both clinical application and understanding of the mechanisms underlying pregnancy related diseases. Methods and Results: In this study, differently expressed genes (DEGs) were found in the MSCs after exposure to E2. Then, Gene Ontology (GO) and Kyoto Encyclopedia of Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The latter is a crucial signal in cell fate, inflammation, and many other bioactivities, and is also greatly involved in the growth and differentiation of MSCs. (39). In colorectal cancer, ADCY2 could also be an important prognostic marker (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is a crucial signal in cell fate, inflammation, and many other bioactivities, and is also greatly involved in the growth and differentiation of MSCs. (39). In colorectal cancer, ADCY2 could also be an important prognostic marker (40).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al. have reported E2-induced ADCY2 as a positive regulator in MSCs ( 39 ). In colorectal cancer, ADCY2 could also be an important prognostic marker ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, a gene whose expression is known to be greatly upregulated in the presence of estradiol, ADCY2, was a candidate gene in the current study. This regulation is mediated by interactions between estradiol and miRNA's that bind to the 3'UTR of ADCY2 (Zhao et al, 2020). The motif analysis presented here found that there are 40 transcription factors predicted to bind to the unique parapatricM.…”
Section: Functional Characterization Of Variants and Motif Analysismentioning
confidence: 71%
“…When investigating PFOA + ZAL-upregulated genes at D50, we noted the presence of one important gene-Adcy2-in multiple signaling pathways. It was reported that estradiol upregulates Adcy2 and, subsequently, promotes the production of cAMP in mesenchymal stem cells [54]. Adcy2 encodes a member of the adenylyl cyclase family, which catalyzes the conversion of ATP to cAMP.…”
Section: Discussionmentioning
confidence: 99%